Clinical psychology for trainees foundations of science-informed practice - Page, Andrew C. 1964- (Cambridge University Press, 2006)
This book describes the practice of clinical psychology with special emphasis on providing trainee therapists with the skills and strategies to achieve the core competencies required for a science-informed clinical practice. It will support the reader in making the transition from the lecture theatre to the consulting room. The approach incorporates a contemporary perspective on the multiple roles of clinical psychologists within a competitive health care market, where professional psychologists not only need to be accountable for their outcomes and efficient in achieving them, but also need to be conscious of the social and political context in which psychology is practised. Chapters are organised around the acquisition of key competencies and linked within an evidence-based, science-informed framework. Case studies, handouts, graphics and worksheets are employed to encourage the implementation of the skills described. This book should be read by all those enrolled in, or contemplating, postgraduate studies in clinical psychology